2021
DOI: 10.2298/tsci200726304n
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development as a challenge of engineering education

Abstract: The purpose of this paper is to research the ways of integrating sustainable development into study programs of engineering faculties in an international context, as well as to analyze the current state of engineering education for sustainable development at the universities of the Republic of Serbia. Therefore, a desktop research, as well as an analysis of the engineering education curricula, have been conducted. The results of the research indicated to two possible approaches to the integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In all the items, approximately between 70 and 95% of the responses are grouped into the first three response levels of the scale (that is in none, in some, and in many subjects), and between 5 and 30% of the answers, at the high levels of the scale (in most and in all subjects). Given that no items' distribution is normal (strong positive asymmetry), median values will be taken into consideration to make comparisons; these values indicate that the central responses have been between no subject (1) and some subject (2). All indicate a low or very low level of insertion of SD in the three analysed degrees.…”
Section: Result Insertion-levelmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the items, approximately between 70 and 95% of the responses are grouped into the first three response levels of the scale (that is in none, in some, and in many subjects), and between 5 and 30% of the answers, at the high levels of the scale (in most and in all subjects). Given that no items' distribution is normal (strong positive asymmetry), median values will be taken into consideration to make comparisons; these values indicate that the central responses have been between no subject (1) and some subject (2). All indicate a low or very low level of insertion of SD in the three analysed degrees.…”
Section: Result Insertion-levelmentioning
confidence: 99%
“…In this current context, the role of engineering students and future professionals is to solve global problems with solutions that respect the environment and social justice, within the limits of environmental sustainability, and without compromising future generations. [2]. All this requires, according to several authors [3][4][5][6], the need to include extensively Sustainable Development (SD) in engineering degrees in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…The current scientific literature also embodies the quest for engineering education in the context of sustainable development concern. Nikolić et al (2021) found out that the number of technical faculties dedicated to the holistic development of engineering competencies for sustainable development is still limited, despite greater recognition of the need and the importance to integrate the concept into the engineering curricula. They advocated for an integrative approach which implies that sustainable development becomes an integral part of the entire curriculum, and a wider intertwining of sustainable concepts as a notion with the regular courses offers greater opportunities for students through raising awareness and responsibility for the environment and the societies.…”
Section: Anti-corruptionmentioning
confidence: 99%
“…(3) Contribution of an enterprise to society [22]; if an enterprise can actively contribute its own power and take part in social welfare activities, it will bring a good reputation to the enterprise, prevent it from being affected by negative comments, and achieve the purpose of sustainable operation. In the knowledge-based economy, the technological capability of a firm should form a part of their sustainable development [23,24].…”
Section: The Sustainable Management Strategymentioning
confidence: 99%